High-corrosion-resistance medical magnesium alloy intravascular stent and preparation method thereof
By adding specific elements to magnesium alloys and using heat treatment technology, the problem of traditional cardiovascular stent materials being prone to inflammation and degradation too quickly is solved, and a high corrosion-resistant magnesium alloy vascular stent is prepared, which improves its tensile strength and resistance Corrosiveness, enhancing the stability and biocompatibility of the stent.
Patent Information
- Application Number
- CN202411485461.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-23
- Publication Date
- 2025-01-10
- Estimated Expiration
- 2044-10-23
AI Technical Summary
Traditional cardiovascular stent materials may trigger an inflammatory response, and magnesium alloys are unable to effectively support the blood vessel walls due to their rapid degradation, resulting in the risk of stent falling off.
By adding elements such as Zn, Si, Eu, Al, Sr and Dy to the magnesium alloy, its tensile strength, corrosion resistance and yield strength are optimized, and solid solution heat treatment and aging treatment methods are used to prepare high corrosion resistance medical products. Magnesium alloy vascular stent.
It improves the tensile strength, corrosion resistance and yield strength of magnesium alloy, delays the degradation speed, enhances the stability and biocompatibility of the stent, and reduces the risk of inflammatory response.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of medical stents, and in particular relates to a high-corrosion-resistant medical magnesium alloy vascular stent and a preparation method thereof. Background Art
[0002] Cardiovascular stents are medical devices used to support blood vessel walls and maintain smooth blood flow. Traditional stents are usually made of metal materials such as stainless steel, nickel-titanium alloy or cobalt-chromium alloy, and have been widely used in clinical practice. However, these metal stents may induce local inflammatory reactions, thereby increasing the risk of late thrombosis.
[0003] To address the above problems, existing technologies have developed drug-coated stents, which can gradually release drugs after implantation in the human body to inhibit the formation of scar tissue around the stent. However, over time, the drug coating will gradually be exhausted, and the exposed metal stent may still cause an inflammatory response. In order to solve the inflammation problem that may be caused by metal stents, magnesium alloys have become one of the ideal choices for this type of new stent due to their good biocompatibility and controllable degradation rate.
[0004] However, magnesium alloy, as one of the few degradable metal materials, cannot fully meet the requirements of an ideal vascular stent material due to its low plastic deformation capacity. In addition, magnesium alloy is prone to corrosion due to its high activity, which is a required characteristic of absorbable vascular implants. Although the fully absorbable stent is originally designed to be eventually absorbed by the body, if the stent degrades too quickly in the body, the absorbable stent may not be able to embed into the blood vessel wall in time to provide the necessary support, but may instead cause the stent to partially fall off and migrate with the blood flow, posing a threat to the patient's life.
[0005] Therefore, there is an urgent need for a highly corrosion-resistant medical magnesium alloy vascular stent and a preparation method thereof. Summary of the invention
[0006] The purpose of the present invention is to provide a high corrosion-resistant medical magnesium alloy vascular stent and a preparation method thereof.
[0007] In order to achieve the above object, the present invention provides the following technical solutions: A high corrosion-resistant medical magnesium alloy vascular stent, the stent is made of a magnesium alloy, the magnesium alloy comprises the following components in weight percentage: Zn 0.5-1.7%, Al 0.01-0.04%, Eu 1.14-2.33%, Si 0.07-0.19%, Sr 0.01-0.09%, Dy 0.5-1.4%, and the balance is Mg.
[0008] Further, the sum of the weight percentages of Zn and Si is greater than the weight percentage of Eu.
[0009] The present invention can improve the tensile strength of magnesium alloy by adding Zn, Si and Eu to the magnesium matrix at the same time. Analysis is that when zinc dissolves in the magnesium matrix to form a solid solution, it will hinder the movement of dislocations. Si and Eu can enhance the tensile strength of magnesium alloys by forming a fine and dispersed strengthening phase. However, it is found in experiments that there is a restrictive relationship between the addition amounts of these three elements, and improper addition will reduce the tensile strength of magnesium alloys. When the sum of the weight percentages of Zn and Si is greater than the weight percentage of Eu, the tensile strength of magnesium alloys is better. Analysis is that there is a problem of competing for binding positions between the three elements, resulting in not all added elements being able to effectively play the expected role. Adding too much calcium may affect the stability of the beneficial phase formed by the magnesium matrix and zinc or silicon, while improving the elastic modulus of magnesium alloys.
[0010] Furthermore, the sum of the weight percentages of Al, Sr and Dy is less than 1%.
[0011] In the system of the present invention, when the sum of the weight percentages of Al, Sr and Dy is less than 0.3%, the corrosion resistance of the magnesium alloy can be improved. The analysis shows that the addition of aluminum can change the electrochemical properties of the alloy, strontium can refine the grains in the magnesium alloy, and the grain refinement can reduce the microscopic heterogeneity inside the alloy. The addition of dysprosium can improve the microstructure of the magnesium alloy, making the alloy more uniform, thereby reducing the tendency to corrosion; at the same time, when the sum of the weight percentages of Al, Sr and Dy is less than 1%, the segregation of elements in the aluminum-magnesium alloy can be reduced, and the alloy has better corrosion resistance.
[0012] Furthermore, the weight percentage ratio of Zn:Dy is greater than 1.
[0013] During the test, by adjusting the addition amount of Zn, Si and Eu, as well as Al, Sr and Dy, the tensile strength and corrosion resistance of magnesium alloy can be improved, but the yield strength of magnesium alloy under this condition is not ideal. After a large number of tests, it was found that when the weight percentage ratio of Zn:Dy is greater than 1, the yield strength of magnesium alloy can be improved. This is mainly because the interaction between zinc and dysprosium can better control the morphology and distribution of the precipitated phase, which helps to form a more uniform and fine precipitated phase, while dysprosium helps to maintain the stability and uniformity of distribution of these precipitated phases. The two have a positive effect on improving the yield strength through synergistic effect.
[0014] The present invention provides a method for preparing the highly corrosion-resistant medical magnesium alloy vascular stent, comprising the following steps: (1) Ingredients: Weigh the components of the magnesium alloy according to the proportion, heat and melt them in an argon atmosphere to obtain a magnesium alloy melt; (2) Refining: The magnesium alloy melt is heated to 740-760°C and a refining agent is added for refining; (3) Casting: Casting is then performed, demoulding is performed, and an ingot is obtained; (4) Solution heat treatment: The ingot is subjected to solution heat treatment in an argon atmosphere, and then quenched in water at 25-30°C to obtain an ingot after solution heat treatment; (5) Aging treatment: In an argon atmosphere, the ingot after solution heat treatment is placed in a heating furnace for aging treatment, and then quenched in water at 25-30°C to obtain an ingot after aging treatment; (6) Making magnesium alloy rods: Extruding the aged ingot into magnesium alloy rods with a diameter of 8-12 mm by hot extrusion; (7) Stent production: The magnesium alloy rod is carved and polished to prepare a highly corrosion-resistant medical magnesium alloy vascular stent.
[0015] Furthermore, the heating temperature in step (1) is 710-730°C.
[0016] Furthermore, the amount of the refining agent added in step (2) is 2-3% of the total weight of the magnesium alloy melt. The refining agent was purchased from Jinzhou Shida Flux New Material Co., Ltd.
[0017] Furthermore, the conditions of the solution heat treatment in step (4) are: temperature of 420-440° C. and holding time of 20-25 h.
[0018] The magnesium alloy of the present invention can improve the elongation at break of the magnesium alloy after solution heat treatment under specific conditions. After solution treatment, the alloy elements of the magnesium alloy of the present invention are evenly distributed, which helps to form a more uniform microstructure, reduce weak links in the material, and improve the uniform plastic deformation ability of the material; the appropriate temperature and time can inhibit the formation of unfavorable precipitation phases, avoiding the generation of these phases that may cause embrittlement of the material.
[0019] Furthermore, the aging treatment in step (5) is carried out under the following conditions: keeping the temperature at 220-260° C. for 30-40 hours.
[0020] Furthermore, in step (6), the temperature of hot extrusion is 320-340° C., and the extrusion speed is 0.4-0.6 mm / s.
[0021] Compared with the prior art, the advantages and beneficial effects of the present invention are: 1. The present invention can enhance the tensile strength of magnesium alloy by adding Zn, Si and Eu into the magnesium matrix. When the sum of the weight percentage of Zn and Si is greater than the weight percentage of Eu, the tensile strength of magnesium alloy is better. At the same time, the elastic modulus of magnesium alloy is improved.
[0022] 2. In the system of the present invention, when the sum of the weight percentages of Al, Sr and Dy is less than 0.3%, the corrosion resistance of the magnesium alloy can be improved.
[0023] 3. When the weight percentage ratio of Zn:Dy is greater than 1, the yield strength of the magnesium alloy can be improved.
[0024] 4. The magnesium alloy of the present invention can improve its elongation at break by undergoing solution heat treatment under specific conditions. DETAILED DESCRIPTION
[0025] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0026] Example 1 The present embodiment provides a highly corrosion-resistant medical magnesium alloy vascular stent, which is made of a magnesium alloy. The magnesium alloy includes the following components in percentage by weight: Zn 1.2%, Al 0.02%, Eu 1.20%, Si 0.1%, Sr 0.05%, Dy 0.8%, and the balance is Mg.
[0027] The method for preparing the highly corrosion-resistant medical magnesium alloy vascular stent comprises the following steps: (1) Ingredients: Weigh the components of the magnesium alloy according to the proportion, heat and melt them at 720°C in an argon atmosphere to obtain a magnesium alloy melt; (2) Refining: The magnesium alloy melt is heated to 750°C and a refining agent is added for refining; the amount of the refining agent added is 3% of the total weight of the magnesium alloy melt. The refining agent is purchased from Jinzhou Shida Flux New Materials Co., Ltd., model M15; (3) Casting: Casting is then performed, demoulding is performed, and an ingot is obtained; (4) Solution heat treatment: The ingot is subjected to solution heat treatment in an argon atmosphere at a temperature of 430°C for 23 h, and then quenched in water at 27°C to obtain an ingot after solution heat treatment; (5) Aging treatment: In an argon atmosphere, the ingot after solution heat treatment is placed in a heating furnace for aging treatment: the ingot is kept at 240°C for 36 hours, and then quenched in water at 27°C to obtain an ingot after aging treatment; (6) Making magnesium alloy rods: Extruding the aged ingot into magnesium alloy rods with a diameter of 10 mm by hot extrusion; the hot extrusion temperature is 330 °C and the extrusion speed is 0.5 mm / s; (7) Stent production: The magnesium alloy rod is carved and polished to prepare a highly corrosion-resistant medical magnesium alloy vascular stent.
[0028] Example 2 The present embodiment provides a highly corrosion-resistant medical magnesium alloy vascular stent, which is made of a magnesium alloy. The magnesium alloy includes the following components in percentage by weight: Zn 1.7%, Al 0.01%, Eu 1.5%, Si 0.07%, Sr 0.01%, Dy 0.9%, and the balance is Mg.
[0029] The method for preparing the highly corrosion-resistant medical magnesium alloy vascular stent comprises the following steps: (1) Ingredients: Weigh the components of the magnesium alloy according to the proportion, heat and melt them at 710°C in an argon atmosphere to obtain a magnesium alloy melt; (2) Refining: The magnesium alloy melt is heated to 740°C and a refining agent is added for refining; the amount of the refining agent added is 2% of the total weight of the magnesium alloy melt. The refining agent is purchased from Jinzhou Shida Flux New Materials Co., Ltd., model M15; (3) Casting: Casting is then performed, demoulding is performed, and an ingot is obtained; (4) Solution heat treatment: The ingot is subjected to solution heat treatment in an argon atmosphere at a temperature of 420°C for 20 h, and then quenched in water at 25°C to obtain an ingot after solution heat treatment; (5) Aging treatment: In an argon atmosphere, the ingot after solution heat treatment is placed in a heating furnace for aging treatment: the ingot is kept at 220°C for 30 hours, and then quenched in water at 25°C to obtain an ingot after aging treatment; (6) Making magnesium alloy rods: Extruding the aged ingot into magnesium alloy rods with a diameter of 10 mm by hot extrusion; the hot extrusion temperature is 320°C and the extrusion speed is 0.4 mm / s; (7) Stent production: The magnesium alloy rod is carved and polished to prepare a highly corrosion-resistant medical magnesium alloy vascular stent.
[0030] Example 3 The present embodiment provides a highly corrosion-resistant medical magnesium alloy vascular stent, which is made of a magnesium alloy. The magnesium alloy includes the following components in weight percentage: Zn 1.6%, Al 0.04%, Eu 1.14%, Si 0.19%, Sr 0.09%, Dy 0.5%, and the balance is Mg.
[0031] The method for preparing the highly corrosion-resistant medical magnesium alloy vascular stent comprises the following steps: (1) Ingredients: Weigh the components of the magnesium alloy according to the proportion, heat and melt them at 730°C in an argon atmosphere to obtain a magnesium alloy melt; (2) Refining: The magnesium alloy melt is heated to 760°C and a refining agent is added for refining; the amount of the refining agent added is 3% of the total weight of the magnesium alloy melt. The refining agent is purchased from Jinzhou Shida Flux New Materials Co., Ltd., model M15; (3) Casting: Casting is then performed, demoulding is performed, and an ingot is obtained; (4) Solution heat treatment: The ingot is subjected to solution heat treatment in an argon atmosphere at a temperature of 440°C for 25 h, and then quenched in water at 30°C to obtain an ingot after solution heat treatment; (5) Aging treatment: In an argon atmosphere, the ingot after solution heat treatment is placed in a heating furnace for aging treatment: the ingot is kept at 260°C for 40 hours, and then quenched in 30°C water to obtain an ingot after aging treatment; (6) Making magnesium alloy rods: Extruding the aged ingot into magnesium alloy rods with a diameter of 10 mm by hot extrusion; the hot extrusion temperature is 340°C and the extrusion speed is 0.6 mm / s; (7) Stent production: The magnesium alloy rod is carved and polished to prepare a highly corrosion-resistant medical magnesium alloy vascular stent.
[0032] Comparative Example 1 The difference between this comparative example and Example 1 is that the components are not within the range.
[0033] The magnesium alloy includes the following components in weight percentage: Zn 2.2%, Al 0.02%, Eu 0.6%, Si 0.23%, Sr 0.05%, Dy 0.05%, and the balance is Mg.
[0034] Comparative Example 2 The difference between this comparative example and Example 1 is that the sum of the weight percentages of Al, Sr and Dy is greater than 1%.
[0035] The magnesium alloy includes the following components in weight percentage: Zn 1.2%, Al 0.04%, Eu 1.20%, Si 0.1%, Sr 0.19%, Dy 1.0%, and the balance is Mg.
[0036] Comparative Example 3 The difference between this comparative example and Example 1 is that the sum of the weight percentages of Zn and Si is less than the weight percentage of Eu.
[0037] The magnesium alloy includes the following components in weight percentage: Zn 0.8%, Al 0.02%, Eu 1.20%, Si 0.07%, Sr 0.05%, Dy 0.8%, and the balance is Mg.
[0038] Comparative Example 4 The difference between this comparative example and Example 1 is that the weight percentage ratio of Zn:Dy is less than 1.
[0039] The magnesium alloy includes the following components in weight percentage: Zn 0.5%, Al 0.02%, Eu 0.20%, Si 0.1%, Sr 0.05%, Dy 0.8%, and the balance is Mg.
[0040] Comparative Example 5 The difference between this comparative example and Example 1 is that the conditions of the solution heat treatment are: temperature of 400° C. and holding time of 30 h.
[0041] Comparative Example 6 The difference between this comparative example and Example 1 is that the conditions of the solution heat treatment are: temperature of 460° C. and holding time of 15 h.
[0042] Performance Testing The performance tests were performed on the magnesium alloy bars prepared in Examples 1-3 and Comparative Examples 1-6: The corrosion resistance was determined by referring to ASTM-G31-72 (Hank's simulated body fluid, 37°C); the tensile strength and elongation at break were determined by referring to DINEN10002-1; the elastic modulus was determined by referring to GB / T232-2010; and the yield strength was determined by referring to DIN50106.
[0043] The results are shown in Table 1: Table 1 Performance test results
[0044] From the above performance test results, it can be seen that the comprehensive performance of the magnesium alloy rods of Examples 1-3 is the most outstanding, which is mainly due to the synergistic effect of the components of the magnesium alloy. The degradation rate (corrosion rate) of the material is ideal and can be used as a degradable in vivo implant material.
[0045] According to the ISO10993 method test, the cytotoxicity of the stents prepared in Examples 1-3 is all Grade 2, which means no obvious cytotoxicity, no intradermal irritation, no sensitization and no genetic toxicity.
[0046] However, the comparative examples are obviously inferior to the embodiments in the corresponding performance tests because they do not adopt the necessary technical solutions. It can be seen from Table 1 that the components of the magnesium alloy in comparative example 1 are not within the range, and its comprehensive performance has decreased to varying degrees, especially the corrosion rate is too fast, which affects the support performance of the stent, proving that the synergistic effect between the components improves the performance of the stent; the sum of the weight percentages of Al, Sr and Dy in comparative example 2 is greater than 1%, which affects the corrosion resistance of the magnesium alloy, and the degradation rate of the stent in the body is too slow; the sum of the weight percentages of Zn and Si in comparative example 3 is less than the weight percentage of Eu, which affects the tensile strength and elastic modulus of the magnesium alloy; the weight percentage ratio of Zn:Dy in comparative example 4 is less than 1, and the yield strength of the magnesium alloy decreases; the conditions of the solid solution heat treatment of comparative examples 5 and 6 are different, which affects the elongation at break of the magnesium alloy. The above experimental results further prove the importance of the technical solutions defined in the present invention for its technical effects.
[0047] The above is a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A highly corrosion-resistant medical magnesium alloy vascular stent, characterized in that: The bracket is made of magnesium alloy, which includes the following components in weight percentage: Zn 0.5-1.7%, Al 0.01-0.04%, Eu 1.14-2.33%, Si 0.07-0.19%, Sr 0.01-0.09%, Dy 0.5-1.4%, and the balance is Mg.
2. The highly corrosion-resistant medical magnesium alloy vascular stent according to claim 1, characterized in that: The sum of the weight percentages of Zn and Si is greater than the weight percentage of Eu.
3. The highly corrosion-resistant medical magnesium alloy vascular stent according to claim 2, characterized in that: The sum of the weight percentages of Al, Sr and Dy is less than 1%.
4. The highly corrosion-resistant medical magnesium alloy vascular stent according to claim 3, characterized in that: The weight percentage ratio of Zn:Dy is greater than 1.
5. A method for preparing the highly corrosion-resistant medical magnesium alloy vascular stent according to any one of claims 1 to 4, characterized in that: The following steps are involved: (1) Ingredients: Weigh the components of the magnesium alloy according to the proportion, heat and melt them in an argon atmosphere to obtain a magnesium alloy melt; (2) Refining: The magnesium alloy melt is heated to 740-760°C and a refining agent is added for refining; (3) Casting: Casting is then performed, demoulding is performed, and an ingot is obtained; (4) Solution heat treatment: The ingot is subjected to solution heat treatment in an argon atmosphere, and then quenched in water at 25-30°C to obtain an ingot after solution heat treatment; (5) Aging treatment: In an argon atmosphere, the ingot after solution heat treatment is placed in a heating furnace for aging treatment, and then quenched in water at 25-30°C to obtain an ingot after aging treatment; (6) Making magnesium alloy rods: Extruding the aged ingot into magnesium alloy rods with a diameter of 8-12 mm by hot extrusion; (7) Stent production: The magnesium alloy rod is carved and polished to prepare a highly corrosion-resistant medical magnesium alloy vascular stent.
6. The method for preparing a highly corrosion-resistant medical magnesium alloy vascular stent according to claim 5, characterized in that: The heating temperature in step (1) is 710-730°C.
7. The method for preparing a highly corrosion-resistant medical magnesium alloy vascular stent according to claim 5, characterized in that: The amount of the refining agent added in step (2) is 2-3% of the total weight of the magnesium alloy melt.
8. The method for preparing a highly corrosion-resistant medical magnesium alloy vascular stent according to claim 5, characterized in that: The conditions of the solution heat treatment in step (4) are: temperature of 420-440° C. and holding time of 20-25 h.
9. The method for preparing a highly corrosion-resistant medical magnesium alloy vascular stent according to claim 5, characterized in that: The aging treatment conditions in step (5) are: keeping the temperature at 220-260° C. for 30-40 hours.
10. The method for preparing a highly corrosion-resistant medical magnesium alloy vascular stent according to claim 5, characterized in that: The temperature of the hot extrusion in step (6) is 320-340° C., and the extrusion speed is 0.4-0.6 mm / s.
Citation Information
Patent Citations
Magnesium alloy and resorbable stents containing the same
CN103889474A
Corrosion-resisting magnesium alloy and preparation method thereof
CN108570585A
Mg-RE-series magnesium alloy and preparing method and application thereof
CN109680195A
Sr-containing magnesium alloy
CN110042289A
Biological-corrosion-resistant high-strength and high-toughness magnesium alloy material and preparation method thereof
CN118703853A